Best Answer

The answer to 6b plus 7 times 5-4b plus 1 equals 38. This is taught in math.

Q: 6b plus 7 5b -4b plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

Add the equations: 4a + 4a - 5b + 5b = 7 + 17 ie 8a = 24 a = 3, so b = 1

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

Six take away B times five B plus 30 equals 1. This is a math problem.

If you're solving for b, then you use the quadratic formula to factor out b. In this case, b= -1/4 or -18/12

4b - 9 + 2b + 8 Coefficients are the numbers in front of the variables. Therefore the coefficient of 4b is 4 and the coefficient of 2b is 2. The like terms are 2b and 2b, but also -9 and 8. Constant terms are the ones that do not contain a variable. -9 and 8 are the constants. 4b - 9 + 2b + 8 can be simplified (by combining like terms) to give 2b - 1

Related questions

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

identity.

4b - 1 = -4 + 4b + 3first, simplify and add together what you can.4b - 1 = -1 + 4b4b = 4bbecause 4b is always equal to 4b, the answer is infinite.

Well if it is worded right then 4xb-1+(-4)+4b=4b-1-4+4b=4b+4b-1-4=8b-5

5b+c-43b-2c+1=1-38b-c

1080b3 + 5 = 5*(216b3 + 1) = 5*(6b + 1)(36b2 - 6b + 1)

1-6b+7=14 8-6b =14 -6b =6 -b =1 b =-1

here is how you go about solving it first write down the question 3b+4+5b-1 then change arrangement so that it looks like this 3b+5b+4-1 then solve 8b+3

1/4

ab + 4 + a + 4b factors to (a + 4)(b + 1)

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1

2a-3+4b-2a-b-3+5=3b-1